Neoangiogenesis markers in canine urothelial carcinomas: A cross‐sectional study - Fabio Gentilini; Roberta Salaroli; Raimondo Tornago; Maria Elena Turba; Tolulope Grace Ogundipe; Augusta Zannoni; Monica Forni; Michela Campigli; Tommaso Furlanello (Veterinary Medicine and Science, 2024)
Abstract Background In humans, there is a growing body of evidence that neoangiogenesis is crucial for tumour growth and progression in urothelial carcinomas (UC) which also typically exhibit overactivation of the RAS‐MAPK pathway. In canine UC (cUC), the same pathway has been aberrantly activated due to V595E BRAF variant and BRAF inhibitors has been evaluated as more effective treatment. However, BRAF inhibition is hampered in humans by rapidly occurring of chemoresistance. Targeting angiogenesis has been speculated to increase the effectiveness of BRAF inhibitors and to delay the development of chemoresistance. Objectives This study aimed to investigate the level of angiogenic markers in urine samples of UC affected dogs (n = 15) in comparison to an unmatched control group (n = 16) along with the clinical, morphological and molecular features. Methods In urine, both vascular endothelial growth factor (VEGF) concentration, using an ELISA assay, and MMP2 and 9 activities, using the zymographic assay, were measured. BRAF analysis was carried out using a digital PCR method. Results Urinary VEGF concentration (mean pg/g_uCrea 6.9 ± 27.7 vs. 1074 ± 1797, p < 0.01) and MMP activity (mean 6.8 × 106 ± 9.2 × 106 vs. 2.5 × 107 ± 2.3 × 107, p < 0.05) were higher in affected dogs than in healthy controls. Urinary active MMP9 was significantly correlated with T3 stage, it was absent in dogs with undetectable VEGF and it correlated well with urinary VEGF concentration. In this cohort, 10/10 UC affected dogs exhibited the V595E BRAF variation. Conclusion The findings are consistent with the presence of overactive neoangiogenesis in cUC. Urinary active MMP9 may be suitable for use as tumour progression biomarker. The addition of angiogenesis targeting may be rationale for novel therapeutic strategies.